Efeitos do LRP6 e Frizzled6 na diferenciação endotelial de DPSC - Silva, Gleyce Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the function of Wnt/β-catenin signaling through LRP-6 and Frizzled-6 receptors in the differentiation of dental pulp stem cells from permanent teeth (DPSC) into endothelial cells. DPSC were transduced with EGFP-tagged lentiviral shRNA vectors (LRP6, Frizzled6 or empty vector - control) for experiments. In vitro assay evaluated GSK3-β and β-catenin expression by western blot in rhWnt1 and rhVEGF165 presence, and VEGF and CXCL-8 (IL-8) expression by ELISA. Endothelial markers expression (western blot and PCR) and tube formation were analyzed after endothelial differentiation of DPSCs. In vivo, tooth slices/scaffolds seeded with transduced DPSCs were implanted subcutaneously in back of immunodefficient mice and blood vessels were counted per immunohistochemistry for eGFP and HE staining. Active β- catenin was more expressed in shRNA-LRP6 and shRNA-Frizzled6 than in control cells, and increased with rhVEGF165 and rhWnt1 supplementation. Phosphorylated GSK3-β expression was lower, however also increased or maintained with rhVEGF165 or rhWnt1. VEGF expression was higher in shRNA-Frizzled6 than in control and shRNA-LRP6 (p<0,05), IL8 expression was lower in shRNA-LRP6, with statistically difference of the others cells. Endothelial markers CD31 and VEGFR2 expression decreased in shRNA-LRP6, but VEGFR2 expression increased in shRNAFrizzled6. shRNA-Frizzled6 and shRNA-LRP6 tube formation was lower when compared to control, however shRNA-Frizzled6 had tendency to increase proliferation in 144h. In vivo, shRNA-LRP6 showed fewer blood vessels formed than other cells (p<0,05). Collectively, the results of this study suggest that Wnt/β-catenin signaling regulates endothelial differentiation of DPSC through LRP6

O objetivo deste estudo foi avaliar a função da via de sinalização Wnt/β- catenina através dos receptores LRP6 e Frizzled6 na diferenciação de células-tronco de polpa dental de dentes permanentes (DPSC) em células endoteliais. DPSC foram transduzidas com marcadores eGFP e vetores lentivirais shRNA (LRP6, Frizzled6 ou vetor vazio - controle) para os experimentos. Os testes in vitro avaliaram a expressão de GSK3-β e β- catenina por western blot na presença de rhWnt1 e rhVEGF165 e de VEGF e CXCL-8 (IL-8) por ELISA. A expressão de marcadores endoteliais (western blot e PCR) e formação de túbulos capilares foram analisados após a diferenciação endotelial das DPSCs. In vivo, fatias dentárias/matrizes condutivas semeadas com DPSCs-shRNA foram implantadas em subcutâneo de dorso de camundongos imunodeprimidos por 28 dias e o número de vasos sanguíneos foi determinado por imunohistoquímica para eGFP e coloração por HE. β-catenina ativa foi mais expressa em shRNA-LRP6 e shRNA-Frizzled6 que nas células controle, e sua expressão aumentou com a suplementação com rhVEGF165 e rhWnt1. A expressão de GSK3-β fosforilado foi menor, porém também aumenta ou permanece estável com rhVEGF165 ou rhWnt1. Quanto à expressão de VEGF, em shRNA-Frizzled6 foi maior que nas células controle e em shRNA-LRP6 (p<0,05), enquanto que a expressão de IL8 foi menor em shRNA-LRP6, diferindo estatisticamente das outras células. A expressão dos marcadores endoteliais CD31 e VEGFR2 diminuiu nas células shRNA-LRP6, enquanto que em shRNAFrizzled6 a expressão de VEGFR2 foi aumentada. A formação de túbulos capilares de shRNA-Frizzled6 e shRNA-LRP6 foi menor quando comparado ao controle, porém shRNA-Frizzled6 obteve uma tendência de aumento na proliferação de capilares em 144h. In vivo, DPSC-shRNALRP6 apresentou menor número de capilares formados quando comparados com as outras duas...
Keywords: Engenharia tecidual; Vasos sanguineos; Células-tronco; Tissue engineering